Die steel additive for forming die-casting die core and manufacturing method of die steel additive

By introducing nano-ceramic particles into mold steel and using selective laser melting technology, the problems of poor high-temperature strength and poor resistance to alternating hot and cold fatigue of existing mold steel are solved, achieving high strength, high toughness and good thermal fatigue properties. Mold steel.

CN119328164AActive Publication Date: 2025-01-21JILIN UNIVERSITY

Patent Information

Application Number
CN202411584533.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-07
Publication Date
2025-01-21
Estimated Expiration
2044-11-07

AI Technical Summary

Technical Problem

The existing mold steel has poor high-temperature strength and poor fatigue resistance to alternate cold and heat, resulting in reduced mold life and early failure.

Method used

A master alloy method is used to introduce trace amounts of nano-ceramic particles, and nano-particle-reinforced mold steel additives are prepared through selective laser melting technology to improve the strength and toughness of the mold steel.

Benefits of technology

The grain size of the mold steel is increased, the grain boundaries are increased, the dislocation movement is hindered, the strength and oxidation resistance of the material are enhanced, and the thermal fatigue performance is improved.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119328164A_ABST
    Figure CN119328164A_ABST
Patent Text Reader

Abstract

The invention discloses a die steel additive material for forming a die-casting die core and a manufacturing method of the die steel additive material, and belongs to the technical field of laser advanced manufacturing, and the manufacturing method comprises the following steps: Al powder, Ti powder and boron carbide are mixed, coated and pre-pressed to obtain a pressing block, and the pressing block is heated to generate a combustion synthesis reaction to obtain a TiC + TiB2 / Al intermediate alloy; heating and remelting die steel, adding the TiC + TiB2 / Al intermediate alloy to obtain molten steel, and pouring the molten steel to obtain nano-particle die steel; heating and remelting the nano-particle die steel to obtain a nano-particle die steel solution, and introducing nitrogen for atomization to obtain nano-particle reinforced powder; the nano-particle reinforced powder is prepared through selective laser melting, and the die steel additive is obtained; the die steel disclosed by the invention has high compactness forming and high strength and toughness.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the field of laser advanced manufacturing technology, and in particular relates to a die steel additive for forming a die casting core and a manufacturing method thereof. Background Art

[0002] "Modern industry, molds are leading", molds are widely used in the fields of automobiles, aviation, navigation, etc. The traditional method of producing molds has a series of problems such as many processes, long cycles, and difficult processing, which cannot meet the needs of modern industrial development. The development of SLM technology provides a new choice for forming molds. The unique laser processing method of SLM can also produce unique microstructures and good mechanical properties. At present, there are few commercial mold steel powders in my country, mainly H13 and 18Ni300. At present, these mold steels have certain problems, such as poor high-temperature strength and poor resistance to alternating cold and hot fatigue, which lead to reduced mold life and premature failure of the mold. Therefore, the development of new high-performance mold steel powders has important practical significance for SLM forming mold technology. Summary of the invention

[0003] Nano-ceramic particles have been proven to effectively improve the comprehensive performance of mold steel. Studies have shown that the traditional method is to use external addition or in-situ endogenous ceramic particles, which requires the addition of a higher volume fraction of ceramic particles to resist the load, but high volume fractions of ceramic particles will have an adverse effect on the toughness of the steel. Therefore, in the process of developing new mold steel powder, we proposed to use the intermediate alloy method to introduce trace nano-ceramic particles to improve the strength and toughness of mold steel powder after forming, and developed a new type of high-performance hot working mold steel powder.

[0004] In view of the deficiencies in the prior art, the present invention proposes a die steel additive for forming a die casting core and a manufacturing method thereof.

[0005] A method for manufacturing a die steel additive for die casting core forming, comprising the following steps:

[0006] (1) Al powder, Ti powder and boron carbide are mixed, coated, and pre-pressed to obtain a compact, and the compact is heated to undergo a combustion synthesis reaction to obtain TiC+TiB 2 / Al master alloy;

[0007] (2) Heat and remelt the mold steel, add the above TiC+TiB 2 / Al master alloy, obtain molten steel, and cast the molten steel to obtain nanoparticle mold steel;

[0008] (3) heating and remelting the nanoparticle mold steel to obtain a nanoparticle mold steel solution, introducing nitrogen gas into the solution for atomization to obtain a nanoparticle reinforced powder;

[0009] (4) The above-mentioned nanoparticle reinforced powder is prepared by selective laser melting to obtain a mold steel additive.

[0010] Preferably, the combustion synthesis reaction environment is a vacuum environment.

[0011] Preferably, the heating and remelting temperature in step (2) and step (3) is 1650°C.

[0012] Preferably, the pressure of the nitrogen is 4 MPa.

[0013] Preferably, the coating material is aluminum foil.

[0014] Preferably, the mass ratio of the Al powder, Ti powder and boron carbide is 24:6:70.

[0015] A die steel additive for die casting core forming, comprising the following chemical compositions in mass percentage: TiC and TiB 2 :0.02-0.05wt.%;C:0.48-0.53wt.%;And Mo:2.8-3.0wt.%。

[0016] Preferably, the following chemical components are also included in mass percentage: Si: 0.3wt.%; Mn:

[0017] 0.20-0.40wt.%; P:0.015wt.%; S:0.002wt.%; Cr4.5-5.0wt.%; V:0.55-0.65wt.%; Cu:0.05wt.% and Fe.

[0018] Application of the above-mentioned mold steel additive material or the mold steel additive material obtained by the above-mentioned manufacturing method in the production of die-casting mold cores.

[0019] The beneficial effects of the mold steel additive of the present invention include:

[0020] During the SLM forming process, nanoparticle-reinforced hot working die steel is subjected to the combined action of laser and nanoparticles, and it can be found that its grain size is much smaller than that of die steel obtained by conventional methods, thereby increasing its grain boundaries. The increase in grain boundaries will hinder the movement of dislocations in the material, thereby improving the strength of the material; the presence of nanoparticles accelerates the dispersion and precipitation of fine carbides, but since the thermal expansion coefficients of carbides and nanoparticles are different from those of hot working die steel, greater stress will be generated around the carbides during the SLM forming process, resulting in a large number of geometric dislocations around the carbides, thereby producing thermal mismatch strengthening; in the SLM forming process of nanoparticle-reinforced die steel, laser processing is a rapid cold processing, and fine dispersed precipitate phases are generated during the processing, which have a pinning effect on dislocations and hinder the slip of dislocations. The mold of the present invention has high strength, high oxidation resistance and high thermal fatigue resistance. BRIEF DESCRIPTION OF THE DRAWINGS

[0021] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, for ordinary technicians in this field, other drawings can be obtained based on these drawings without paying any creative work.

[0022] Figure 1 This is the morphology of the mold steel powder in Example 1.

[0023] Figure 2 This is a metallographic photograph of the die steel in Example 1.

[0024] Figure 3 is the laser absorptivity of the mold steel powder in Example 1.

[0025] Figure 4 Room temperature tensile curves of various examples.

[0026] Figure 5 High temperature tensile curves of various examples. DETAILED DESCRIPTION

[0027] The following will be combined with the drawings in the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0028] Embodiment 1:

[0029] Design of nanoparticle reinforced mold steel additive powder: Prepare nanoparticle master alloy, mix Al powder, Ti powder and boron carbide in a mass ratio of 24:6:70, put the mixed powder into a high-energy ball mill, mix it evenly at a speed of 40r / min for 48 hours, and cover the mixed powder with aluminum foil.

[0030] Pre-pressing is performed on a hydraulic testing machine to obtain a cold pressed block, which is then placed in a graphite mold and heated in a vacuum sintering furnace to undergo a combustion synthesis reaction, ultimately obtaining TiC+TiB 2 / Al master alloy.

[0031] The chemical composition and mass percentage of the high-performance mold steel are: C: 0.48wt.%; Si: 0.30wt.%; Mn: 0.4wt.%; P: 0.015wt.%; S: 0.002wt.%; Cr: 4.5wt.%; Mo: 3.0wt.%; V: 0.55wt.%; Cu: 0.05wt.%; the balance is Fe.

[0032] High-performance mold steel is cut into 2kg blocks and remelted in the furnace of a medium-frequency induction furnace. 2 / Al master alloy is added into a medium frequency induction furnace to obtain molten steel. When the temperature is about 1650℃, the molten steel is uniformly injected into a ladle at about 1500℃. Nano-TiC+TiB2 particles are dispersed in the molten steel as the molten steel boils. Al acts as a deoxidizer to generate aluminum oxides floating above the molten steel. The molten steel is then poured into a sand mold to obtain a molten steel with a content of 0.02wt.% TiC and TiB2. 2 Strengthened mold steel.

[0033] Preparation of nanoparticle-reinforced powders:

[0034] The obtained nanoparticle reinforced mold steel is put into the furnace of a medium frequency induction furnace for remelting, the nanoparticle reinforced mold steel is heated to a liquid state, and after being maintained at 1650° C. for 2 minutes, a nanoparticle reinforced mold steel melt is obtained.

[0035] In a nitrogen environment, the obtained molten metal is transferred to the tundish, and the molten metal freely flows downward from the opening at the bottom of the tundish with a diameter of about 4 mm. Then, nitrogen gas with a pressure of about 4 MPa is introduced into the sealed channel. The nitrogen gas can blow away the freely flowing molten metal and realize the nitrogen atomization process. After free fall, the atomized molten metal is cooled at the bottom to form nanoparticle-reinforced powder.

[0036] The obtained powder is then sieved and divided into two parts for sieving, and the sieving requirements are 15-53 μm and 53-150 μm respectively.

[0037] The size of the laser additive powder selected later was 15-53 μm, and the absorption rate of the 1064 laser band was 36.43%. Figure 3 The selective laser melting technology is used for preparation, with a fixed laser power of 200W, a scanning speed of 900mm / s, a powder layer thickness of 30μm, a laser scanning interval of 100μm, and a laser scanning strategy of 70° interlayer rotation, so that the component can be formed with high density.

[0038] The properties of the final mold steel are shown in Table 1. The Rockwell hardness tester (300HRSS-150) of Laizhou Huayin Testing Instrument Co., Ltd. was used to measure the Rockwell hardness of the sample. The sample was polished smooth before the test to ensure that the upper and lower surfaces were parallel. During the test, the test force was 150kgf, and the test force was maintained for 5s. Eight points were randomly selected on the sample to measure its hardness. After removing the maximum and minimum values, the average value was taken as the final hardness value of the sample. The room temperature hardness measured by the Rockwell hardness tester was 56.87HRC. The sample was made into a standard tensile sample size, the surface was polished smooth with sandpaper, and the tensile test was carried out using a servo hydraulic material testing system. The tensile speed was 10 -4 s -1 The tensile strength is 1766MPa and the yield strength is 999MPa at room temperature (20℃), and the tensile strength is 1471MPa and the yield strength is 1413MPa at high temperature (550℃).

[0039] Embodiment 2:

[0040] Design of nanoparticle reinforced mold steel additive powder: Prepare nanoparticle master alloy, mix Al powder, Ti powder and boron carbide in a mass ratio of 24:6:70, put the mixed powder into a high-energy ball mill, mix it evenly at a speed of 40r / min for 36 hours, and cover the mixed powder with aluminum foil.

[0041] Pre-pressing is performed on a hydraulic testing machine to obtain a cold pressed block, which is then placed in a graphite mold and heated in a vacuum sintering furnace to undergo a combustion synthesis reaction, ultimately obtaining TiC+TiB 2 / Al master alloy.

[0042] The chemical composition and mass percentage of the high-performance mold steel are: C: 0.53wt.%; Si: 0.3wt.%; Mn: 0.2wt.%; P: 0.015wt.%; S: 0.002wt.%; Cr: 5.0wt.%; Mo: 2.8wt.%; V: 0.65wt.%; Ti: 0.005wt.%; Cu: 0.05wt.%; the balance is Fe.

[0043] High-performance mold steel is cut into blocks of 1 kg and remelted in the furnace of a medium-frequency induction furnace. 2 / Al master alloy is added into a medium frequency induction furnace to obtain molten steel. When the temperature is about 1650℃, the molten steel is uniformly injected into the ladle at about 1500℃. Nano-TiC+TiB2 particles are dispersed in the molten steel as the molten steel boils. Al acts as a deoxidizer to generate aluminum oxide floating above the molten steel. The molten steel is then poured into a sand mold to obtain a molten steel with a content of 0.05wt.% TiC and TiB2. 2 Strengthened mold steel.

[0044] Preparation of nanoparticle-reinforced powders:

[0045] The obtained nanoparticle reinforced mold steel is put into the furnace of a medium frequency induction furnace for remelting, the nanoparticle reinforced mold steel is heated to a liquid state, and after being maintained at 1600° C. for 3 minutes, a nanoparticle reinforced mold steel melt is obtained.

[0046] In a nitrogen environment, the obtained molten metal is transferred to the tundish, and the molten metal freely flows downward from the opening at the bottom of the tundish with a diameter of about 4 mm. Then, nitrogen gas with a pressure of about 4 MPa is introduced into the sealed channel. The nitrogen gas can blow away the freely flowing molten metal and realize the nitrogen atomization process. After free fall, the atomized molten metal is cooled at the bottom to form nanoparticle-reinforced powder.

[0047] The obtained powder is then sieved and divided into two parts for sieving, and the sieving requirements are 15-53 μm and 53-150 μm respectively.

[0048] The size of the laser additive powder selected subsequently was: 15-53μm, and it was prepared using selective laser melting technology. The laser power was fixed at 200W, the scanning speed was 1000mm / s, the powder layer thickness was fixed at 30μm, the laser scanning interval was fixed at 100μm, and the laser scanning strategy was a 70° interlayer rotation, so that the components achieved high-density forming.

[0049] The properties of the final mold steel are shown in Table 1. The Rockwell hardness tester (300HRSS-150) of Laizhou Huayin Testing Instrument Co., Ltd. was used to measure the Rockwell hardness of the sample. The sample was polished smooth before the test to ensure that the upper and lower surfaces were parallel. During the test, the test force was 150kgf, and the test force was maintained for 5s. Eight points were randomly selected on the sample to measure its hardness. After removing the maximum and minimum values, the average value was taken as the final hardness value of the sample. The room temperature hardness measured by the Rockwell hardness tester was 56.79HRC. The sample was made into a standard tensile sample size, the surface was polished smooth with sandpaper, and the tensile test was carried out using a servo hydraulic material testing system. The tensile speed was 10 -4 s -1 The tensile strength is 1482MPa and the yield strength is 985MPa at room temperature (20℃), and the tensile strength is 1414MPa and the yield strength is 1257MPa at high temperature (550℃).

[0050] Embodiment 3:

[0051] Design of nanoparticle reinforced mold steel additive powder: Prepare nanoparticle master alloy, mix Al powder, Ti powder and boron carbide in a mass ratio of 24:6:70, put the mixed powder into a high-energy ball mill, mix it evenly at a speed of 40r / min for 48 hours, and cover the mixed powder with aluminum foil.

[0052] Pre-pressing is performed on a hydraulic testing machine to obtain a cold pressed block, which is then placed in a graphite mold and heated in a vacuum sintering furnace to undergo a combustion synthesis reaction, ultimately obtaining TiC+TiB 2 / Al master alloy.

[0053] The chemical composition and mass percentage of the high performance mold steel are: C: 0.50wt.%; Si: 0.3wt.%; Mn: 0.3wt.%; P: 0.015wt.%; S: 0.002wt.%; Cr: 4.8wt.%; Mo: 2.9wt.%; V: 0.59wt.%; Cu: 0.05wt.%; the balance is Fe.

[0054] High-performance mold steel is cut into 2kg blocks and remelted in the furnace of a medium-frequency induction furnace. 2 / Al master alloy is added into the medium frequency induction furnace to obtain molten steel. When the temperature is about 1650℃, the molten steel is uniformly injected into the ladle at about 1500℃. Nano-TiC+TiB2 particles are dispersed in the molten steel as the molten steel boils. Al acts as a deoxidizer to generate aluminum oxide floating above the molten steel. The molten steel is then poured into the sand mold with a content of 0.02wt.% TiC and TiB 2 Strengthened mold steel.

[0055] Preparation of nanoparticle-reinforced powders:

[0056] The obtained nanoparticle reinforced mold steel is put into the furnace of a medium frequency induction furnace for remelting, the nanoparticle reinforced mold steel is heated to a liquid state, and after being maintained at 1650° C. for 2 minutes, a nanoparticle reinforced mold steel melt is obtained.

[0057] In a nitrogen environment, the obtained molten metal is transferred to the tundish, and the molten metal freely flows downward from the opening at the bottom of the tundish with a diameter of about 4 mm. Then, nitrogen gas with a pressure of about 4 MPa is introduced into the sealed channel. The nitrogen gas can blow away the freely flowing molten metal and realize the nitrogen atomization process. After free fall, the atomized molten metal is cooled at the bottom to form nanoparticle-reinforced powder.

[0058] The obtained powder is then sieved and divided into two parts for sieving, and the sieving requirements are 15-53 μm and 53-150 μm respectively.

[0059] The size of the laser additive powder selected was 15-53μm. It was prepared using selective laser melting technology, with a fixed laser power of 200W, a scanning speed of 900mm / s, a powder layer thickness of 30μm, a laser scanning interval of 100μm, and a laser scanning strategy of 70° interlayer rotation to achieve high-density forming of the component.

[0060] The printed high-density forming die steel is subjected to tempering heat treatment to eliminate internal residual stress. The tempering heat treatment steps are as follows: the forming die steel is placed in a heat treatment furnace, the heating rate is set to 12°C / min, the temperature is raised to 625°C, and after keeping warm for 120 minutes, the sample is taken out and air-cooled to room temperature.

[0061] The properties of the final mold steel are shown in Table 1. The Rockwell hardness tester (300HRSS-150) of Laizhou Huayin Testing Instrument Co., Ltd. was used to measure the Rockwell hardness of the sample. The sample was polished smooth before the test to ensure that the upper and lower surfaces were parallel. During the test, the test force was 150kgf, and the test force was maintained for 5s. Eight points were randomly selected on the sample to measure its hardness. After removing the maximum and minimum values, the average value was taken as the final hardness value of the sample. The room temperature hardness measured by the Rockwell hardness tester was 56.87HRC. The sample was made into a standard tensile sample size, the surface was polished smooth with sandpaper, and the tensile test was carried out using a servo hydraulic material testing system. The tensile speed was 10 -4 s -1 The tensile strength is 1766MPa and the yield strength is 999MPa at room temperature (20℃), and the tensile strength is 1471MPa and the yield strength is 1413MPa at high temperature (550℃).

[0062] Embodiment 4:

[0063] Design of nanoparticle reinforced mold steel additive powder: Prepare nanoparticle master alloy, mix Al powder, Ti powder and boron carbide in a mass ratio of 24:6:70, put the mixed powder into a high-energy ball mill, mix it evenly at a speed of 40r / min for 48 hours, and cover the mixed powder with aluminum foil.

[0064] Pre-pressing is performed on a hydraulic testing machine to obtain a cold pressed block, which is then placed in a graphite mold and heated in a vacuum sintering furnace to undergo a combustion synthesis reaction, ultimately obtaining TiC+TiB 2 / Al master alloy.

[0065] The chemical composition and mass percentage of the high performance mold steel are: C: 0.50wt.%; Si: 0.3wt.%; Mn: 0.3wt.%; P: 0.015wt.%; S: 0.002wt.%; Cr: 4.8wt.%; Mo: 2.9wt.%; V: 0.59wt.%; Cu: 0.05wt.%; the balance is Fe.

[0066] High-performance mold steel is cut into 2kg blocks and remelted in the furnace of a medium-frequency induction furnace. 2 / Al master alloy is added into a medium frequency induction furnace to obtain molten steel. When the temperature is about 1650℃, the molten steel is uniformly injected into a ladle at about 1500℃. Nano-TiC+TiB2 particles are dispersed in the molten steel as the molten steel boils. Al acts as a deoxidizer to generate aluminum oxides floating above the molten steel. The molten steel is then poured into a sand mold to obtain a molten steel with a content of 0.02wt.% TiC and TiB2. 2 Strengthened mold steel.

[0067] Preparation of nanoparticle-reinforced powders:

[0068] The obtained nanoparticle reinforced mold steel is put into the furnace of a medium frequency induction furnace for remelting, the nanoparticle reinforced mold steel is heated to a liquid state, and after being maintained at 1650° C. for 2 minutes, a nanoparticle reinforced mold steel melt is obtained.

[0069] In a nitrogen environment, the obtained molten metal is transferred to the tundish, and the molten metal freely flows downward from the opening at the bottom of the tundish with a diameter of about 4 mm. Then, nitrogen gas with a pressure of about 4 MPa is introduced into the sealed channel. The nitrogen gas can blow away the freely flowing molten metal and realize the nitrogen atomization process. After free fall, the atomized molten metal is cooled at the bottom to form nanoparticle-reinforced powder.

[0070] The obtained powder is then sieved and divided into two parts for sieving, and the sieving requirements are 15-53 μm and 53-150 μm respectively.

[0071] The size of the laser additive powder selected was 15-53μm. It was prepared using selective laser melting technology, with a fixed laser power of 200W, a scanning speed of 900mm / s, a powder layer thickness of 30μm, a laser scanning interval of 100μm, and a laser scanning strategy of 70° interlayer rotation to achieve high-density forming of the component.

[0072] The printed high-density forming die steel is subjected to tempering heat treatment to eliminate internal residual stress. The tempering heat treatment steps are as follows: the forming die steel is placed in a heat treatment furnace, the heating rate is set to 10°C / min, the temperature is raised to 600°C, and after keeping the temperature for 120 minutes, the sample is taken out and air-cooled to room temperature;

[0073] The properties of the final mold steel are shown in Table 1. The Rockwell hardness tester (300HRSS-150) of Laizhou Huayin Testing Instrument Co., Ltd. was used to measure the Rockwell hardness of the sample. The sample was polished smooth before the test to ensure that the upper and lower surfaces were parallel. During the test, the test force was 150kgf, and the test force was maintained for 5s. Eight points were randomly selected on the sample to measure its hardness. After removing the maximum and minimum values, the average value was taken as the final hardness value of the sample. The room temperature hardness measured by the Rockwell hardness tester was 58.65HRC. The sample was made into a standard tensile sample size, the surface was polished smooth with sandpaper, and the tensile test was carried out using a servo hydraulic material testing system. The tensile speed was 10 -4 s -1 The tensile strength is 2380MPa and the yield strength is 1766MPa at room temperature (20℃), and the tensile strength is 1671MPa and the yield strength is 1450MPa at high temperature (550℃).

[0074] Embodiment 5:

[0075] Design of nanoparticle reinforced mold steel additive powder: Prepare nanoparticle master alloy, mix Al powder, Ti powder and boron carbide in a mass ratio of 24:6:70, put the mixed powder into a high-energy ball mill, mix it evenly at a speed of 40r / min for 48 hours, and cover the mixed powder with aluminum foil.

[0076] Pre-pressing is performed on a hydraulic testing machine to obtain a cold pressed block, which is then placed in a graphite mold and heated in a vacuum sintering furnace to undergo a combustion synthesis reaction, ultimately obtaining TiC+TiB 2 / Al master alloy.

[0077] The chemical composition and mass percentage of the high performance mold steel are: C: 0.50wt.%; Si: 0.3wt.%; Mn: 0.3wt.%; P: 0.015wt.%; S: 0.002wt.%; Cr: 4.8wt.%; Mo: 2.9wt.%; V: 0.59wt.%; Cu: 0.05wt.%; the balance is Fe.

[0078] High-performance mold steel is cut into 2kg blocks and remelted in the furnace of a medium-frequency induction furnace. 2 / Al master alloy is added into the medium frequency induction furnace to obtain molten steel. When the temperature is about 1650℃, the molten steel is uniformly injected into the ladle at about 1500℃. Nano-TiC+TiB2 particles are dispersed in the molten steel as the molten steel boils. Al acts as a deoxidizer to generate aluminum oxide floating above the molten steel. The molten steel is then poured into a sand mold to obtain a molten steel with a content of 0.02% TiC and TiB 2 Strengthened mold steel.

[0079] Preparation of nanoparticle-reinforced powders:

[0080] The obtained nanoparticle reinforced mold steel is put into the furnace of a medium frequency induction furnace for remelting, the nanoparticle reinforced mold steel is heated to a liquid state, and after being maintained at 1650° C. for 2 minutes, a nanoparticle reinforced mold steel melt is obtained.

[0081] In a nitrogen environment, the obtained molten metal is transferred to the tundish, and the molten metal freely flows downward from the opening at the bottom of the tundish with a diameter of about 4 mm. Then, nitrogen gas with a pressure of about 4 MPa is introduced into the sealed channel. The nitrogen gas can blow away the freely flowing molten metal and realize the nitrogen atomization process. After free fall, the atomized molten metal is cooled at the bottom to form nanoparticle-reinforced powder.

[0082] The obtained powder is then sieved and divided into two parts for sieving, and the sieving requirements are 15-53 μm and 53-150 μm respectively.

[0083] The size of the laser additive powder selected was 15-53μm. It was prepared using selective laser melting technology. The laser power was fixed at 200W, the scanning speed was 900mm / s, the powder layer thickness was fixed at 30μm, the laser scanning interval was fixed at 100μm, and the laser scanning strategy was a 70° interlayer rotation to achieve a highly dense component.

[0084] The printed high-density forming die steel is subjected to tempering heat treatment to eliminate internal residual stress. The tempering heat treatment steps are as follows: the forming die steel is placed in a heat treatment furnace, the heating rate is set to 12°C / min, the temperature is raised to 650°C, and after keeping the temperature for 120 minutes, the sample is taken out and air-cooled to room temperature;

[0085] The properties of the final mold steel are shown in Table 1. The Rockwell hardness tester (300HRSS-150) of Laizhou Huayin Testing Instrument Co., Ltd. was used to measure the Rockwell hardness of the sample. The sample was polished smooth before the test to ensure that the upper and lower surfaces were parallel. During the test, the test force was 150kgf, and the test force was maintained for 5s. Eight points were randomly selected on the sample to measure its hardness. After removing the maximum and minimum values, the average value was taken as the final hardness value of the sample. The room temperature hardness measured by the Rockwell hardness tester was 48.1HRC. The sample was made into a standard tensile sample size, the surface was polished smooth with sandpaper, and the tensile test was carried out using a servo hydraulic material testing system. The tensile speed was 10 -4 s -1 The tensile strength is 1640MPa and the yield strength is 1368MPa at room temperature (20℃), and the tensile strength is 957MPa and the yield strength is 871MPa at high temperature (550℃).

[0086] Table 1 Performance indexes of mold steel obtained in Examples 1-5

[0087]

[0088]

[0089] From the experimental data in Table 1, it can be seen that in each embodiment, the density exceeds 99%, which indicates that the powder has better powder compactness and formability. The printed state of the powder forming also has better strength before tempering. By selecting a laser forming parameter and subjecting it to different heat treatment temperatures, its strength will decrease with the increase of tempering temperature, but the plastic toughness will increase with the increase of tempering temperature.

[0090] In the description of this specification, the description with reference to the terms "one embodiment", "example", "specific example", etc. means that the specific features, structures, materials or characteristics described in conjunction with the embodiment or example are included in at least one embodiment or example of the present invention. In this specification, the schematic representation of the above terms does not necessarily refer to the same embodiment or example. Moreover, the specific features, structures, materials or characteristics described can be combined in any one or more embodiments or examples in a suitable manner.

[0091] The above shows and describes the basic principles, main features and advantages of the present invention. Those skilled in the art should understand that the present invention is not limited to the above embodiments, and the above embodiments and descriptions are only for explaining the principles of the present invention. Without departing from the spirit and scope of the present invention, the present invention may have various changes and improvements, and these changes and improvements all fall within the scope of the present invention to be protected.

Claims

1. A method for manufacturing a die steel additive for die casting core formation, characterized in that: The following steps are involved: (1) Al powder, Ti powder and boron carbide are mixed, coated, and pre-pressed to obtain a compact, and the compact is heated to undergo a combustion synthesis reaction to obtain a TiC+TiB2 / Al master alloy; (2) heating and remelting the mold steel, adding the above-mentioned TiC+TiB2 / Al master alloy to obtain molten steel, and pouring the molten steel to obtain nanoparticle mold steel; (3) heating and remelting the nanoparticle mold steel to obtain a nanoparticle mold steel solution, introducing nitrogen gas into the solution for atomization to obtain a nanoparticle reinforced powder; (4) The above-mentioned nanoparticle reinforced powder is prepared by selective laser melting to obtain a mold steel additive.

2. The method for manufacturing a die steel additive for forming a die casting core according to claim 1, characterized in that: The environment of the combustion synthesis reaction is a vacuum environment.

3. The manufacturing method of die steel additive for die casting core formation according to claim 1, characterized in that: The heating and remelting temperature in the steps (2) and (3) is 1650°C.

4. The method for manufacturing a die steel additive for forming a die casting core according to claim 1, characterized in that: The pressure of the nitrogen is 4 MPa.

5. The method for manufacturing a die steel additive for forming a die casting core according to claim 1, characterized in that: The coating material is aluminum foil.

6. The method for manufacturing a die steel additive for forming a die casting core according to claim 1, characterized in that: The mass ratio of the Al powder, Ti powder and boron carbide is 24:6:

70.

7. A die steel additive for die casting core formation, characterized in that: The chemical composition includes the following mass percentages: TiC and TiB2: 0.02-0.05wt.%; C: 0.48-0.53wt.% and Mo: 2.8-3.0wt.%.

8. The die steel additive for forming a die casting core according to claim 7, characterized in that: It also includes the following chemical components in mass percentage: Si: 0.3wt.%; Mn: 0.20-0.40wt.%; P: 0.015wt.%; S: 0.002wt.%; Cr4.5-5.0wt.%; V: 0.55-0.65wt.%; Cu: 0.05wt.% and Fe.

9. Use of the mold steel additive material according to any one of claims 7 to 8 or the mold steel additive material produced by the manufacturing method according to any one of claims 1 to 6 in the production of die-casting mold cores.

Citation Information

Patent Citations

  • BE661802A

  • Aluminum alloy welding wire rod containing micro-nano TiC-TiB2 particles

    CN108080811A

  • Method of in-situ micro biphase nanometer ceramic particle strengthened steel

    CN109023082A

  • Preparation method of Bi-directional vertical controlled rolling trace TiC-TiB2 reinforced Al-Si-Mg alloy plate

    CN109536769A

  • Controlled rolling preparation method of trace micro-nano hybrid particle reinforced Al-Cu-Mg-Si board

    CN109609798A

Cited By

  • Additive manufacturing die steel with high oxidation resistance and thermal fatigue resistance and preparation method

    CN120082788A

  • A high-oxidation- and thermal-fatigue-resistant additive manufacturing die steel and its preparation method

    CN120082788B